Pressure-sensitive adhesive composition and method for preparing same and use in flexible organic light-emitting diodes - Patents.com
Through a specific composition of the pressure-sensitive adhesive composition, the problem of fragile layer protection in the manufacturing of flexible OLED displays is solved, and low initial adhesion, high adhesion stability and low mobility are achieved, so as to protect the fragile layer from damage, and is suitable for processing of flexible OLED displays.
Patent Information
- Application Number
- JP2024541161
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-01-26
- Filing Date
- 2022-11-18
- Publication Date
- 2025-02-12
AI Technical Summary
Protecting fragile layers from damage (such as scratches or other impacts) is a key issue in the manufacturing process of flexible OLED displays, and the prior art is difficult to provide low initial adhesion and high adhesion stability during processing, while avoiding interlayer separation caused by increased adhesion.
The pressure-sensitive adhesive composition containing a specific proportion of alkenyl polydimethylsiloxane glue, an alkenyl polydimethylsiloxane polymer, a polyalkyl hydrosiloxane, a platinum group metal catalyst, an aldehyde alcohol and an organic solvent is prepared by a hydrogen silanization reaction to form a protective film with low initial adhesion, high adhesion stability and low mobility.
It realizes the protection of fragile layers from damage during the OLED manufacturing process, while ensuring low initial adhesion, long-term adhesion stability and low mobility, avoiding interlayer separation caused by increased adhesion, and meeting the processing needs of flexible OLED displays.
Smart Images

Figure 2025504394000001 
Figure 2025504394000002 
Figure 2025504394000003
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims the benefit under 35 U.S.C. §119(e) of U.S. Provisional Patent Application No. 63 / 303,143, filed January 26, 2022. U.S. Provisional Patent Application No. 63 / 303,143 is incorporated herein by reference.
[0002] The present invention relates to a pressure-sensitive adhesive composition useful in a process for fabricating flexible organic light-emitting diode (OLED) displays, which is cured to form a pressure-sensitive adhesive having low initial adhesion, high adhesion stability over time, low migration, scratch resistance and / or repair properties. [Background technology]
[0003] In a typical process for making flexible OLED displays, an OLED is formed on a relatively rigid substrate (e.g., glass or glass coated with a polyimide varnish) and a passivation layer is formed on the surface of the OLED opposite the substrate. During further processing, the rigid substrate is removed. Weak or fragile layers need to be protected from damage (e.g., scratches or other impacts) during further processing.
[0004] To protect layers during the fabrication process, a protective film with low adhesion is desired to prevent delamination of fragile layers (e.g., passivation layers or thin film encapsulation layers) on the surface of an OLED module when the protective film is peeled off after use. If adhesion control fails and adhesion increases over time (i.e., during the fabrication process), layers may delaminate or be damaged when the protective film is removed. Therefore, the industry needs to provide a protective film with low adhesion and high adhesion stability (where adhesion does not increase during the time required for the fabrication process to a degree that would cause delamination or damage).
[0005] It is also important to keep the surface of the layer clean so that additional films or layers can be laminated after the protective film is removed.Therefore, there is a need in the industry to provide protective films with low migration properties (so that no or minimal adhesive from the protective film remains on the surface of the layer of the flexible OLED device after the protective film is removed). Summary of the Invention
[0006] The pressure sensitive adhesive composition comprises an alkenyl-containing polydialkylsiloxane gum, an alkenyl-containing polydialkylsiloxane polymer, a polyalkylhydrogensiloxane, a platinum group metal catalyst, an acetylenic alcohol, and an organic solvent.
[0007] Methods for preparing the pressure-sensitive adhesive compositions, methods for using the pressure-sensitive adhesive compositions to form pressure-sensitive adhesive articles, and methods for using the pressure-sensitive adhesive articles to fabricate flexible organic light emitting diode devices are also disclosed. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] The pressure-sensitive adhesive composition introduced above is (A) a first alkenyl-containing polydialkylsiloxane gum having silicon-bonded alkyl groups having 1 to 10 carbon atoms and silicon-bonded alkenyl groups having 2 to 6 carbon atoms, the vinyl functionality (i.e., CH2=CH in the silicon-bonded alkenyl groups) being present in an amount of 0.03% to 0.11% by weight, based on the weight of the first alkenyl-containing polydialkylsiloxane gum; optionally, (B) a second alkenyl-containing polydialkylsiloxane gum having silicon-bonded alkyl groups having 1 to 10 carbon atoms and silicon-bonded alkenyl groups having 2 to 6 carbon atoms, the vinyl functionality being present in an amount of 0.3% to 1.1% by weight, based on the weight of the second alkenyl-containing polydialkylsiloxane gum; wherein starting materials (A) and (B) are present in amounts sufficient to provide a weight ratio, calculated by (B) / [(A)+(B)], of 0 to 0.5; (C) an alkenyl-containing polydialkylsiloxane polymer having silicon-bonded alkyl groups having 1 to 10 carbon atoms and silicon-bonded alkenyl groups having 2 to 6 carbon atoms, the vinyl functionality being present in an amount of 0.01% to 2% by weight based on the weight of the alkenyl-containing polydialkylsiloxane polymer; wherein starting materials (A), (B), and (C) are present in amounts to provide a weight ratio calculated by [(A)+(B)] / (C)] of 0.5 to 2.5; (D) a polyalkylhydrogensiloxane having silicon-bonded alkyl groups having from 1 to 10 carbon atoms, at least 3 silicon-bonded hydrogen atoms per molecule, and an average of at least 1 weight percent silicon-bonded hydrogen atoms; (E) a platinum group metal catalyst; (F) an acetylenic alcohol; optionally, (G) an adhesion promoter; and (H) an organic solvent, provided that all of the starting materials in the combined composition have a molar ratio of silicon-bonded hydrogen atoms (SiH) to silicon-bonded alkenyl groups (Vi) [SiH / Vi ratio] of from 3.33 to 5.21.
[0009] (A) A first (lower) alkenyl-containing polydialkylsiloxane gum The starting material (A) in the pressure sensitive adhesive composition is a first alkenyl-containing polydialkylsiloxane gum. The first alkenyl-containing polydialkylsiloxane gum has silicon-bonded alkyl groups having 1 to 10 carbon atoms and silicon-bonded alkenyl groups having 2 to 6 carbon atoms. The vinyl (CH2=CH-) functional groups (e.g., in the silicon-bonded alkenyl groups) are present in an amount of 0.03% to 0.11% by weight, based on the weight of the first alkenyl-containing polydialkylsiloxane gum. Alternatively, the (A) first alkenyl-containing polydialkylsiloxane gum may have 0.05% to 0.09% by weight of vinyl functional groups.
[0010] The starting material (A) is a first alkenyl-containing polydialkylsiloxane gum having the unit formula (I): 1 2R 2 SiO 1 / 2 ) d (R 1 3SiO 1 / 2 ) e (R 1 R 2 SiO 2 / 2 ) f (R 1 2SiO 2 / 2 ) g wherein each R 1 are independently an alkyl group of 1 to 10 carbon atoms, and each R 2 are independently alkenyl groups of 2 to 6 carbon atoms, and the subscripts d, e, f, and g represent the average number of each unit in the unit formula and have values such that 2≧d≧0, 2≧e≧0, 20≧f≧5, 10,000≧g≧2,000, and the amount (d+e)=2. Alternatively, the subscript d can be 2 and the subscript e can be 0. Alternatively, the subscript f can be 5 to 15. Alternatively, the subscript g can be 6,000 to 8000, or 6,500 to 7,500.
[0011] In the unit formula (I), each R 1 are independently an alkyl group having 1 to 10 carbon atoms, and each R 2are independently alkenyl groups of 2 to 6 carbon atoms. Suitable alkyl groups include branched or unbranched saturated monovalent hydrocarbon groups. Alkyl is exemplified by, but not limited to, methyl, ethyl, propyl (e.g., isopropyl and / or n-propyl), butyl (e.g., isobutyl, n-butyl, tert-butyl and / or sec-butyl), pentyl (e.g., isopentyl, neopentyl and / or tert-pentyl), hexyl, heptyl, octyl, nonyl, and decyl, as well as branched saturated monovalent hydrocarbon groups of 6 to 10 carbon atoms. Alternatively, each R 1 may be selected from methyl, ethyl, and isopropyl. Alternatively, each R 1 may be methyl. Suitable alkenyl groups include branched or unbranched monovalent hydrocarbon groups having a terminal double bond (vinyl functionality). Alkenyl is exemplified by, but not limited to, vinyl, allyl, butenyl (e.g., isobutenyl, n-butenyl, tert-butenyl, and / or sec-butenyl), and hexenyl, which includes branched and straight chain groups of six carbon atoms. Alternatively, each R 2 is the formula CH2=CH-(CH2) s -, where the subscript s is 0 to 4 (i.e., either vinyl if s=0, or vinyl terminated if s>0). 2 may be vinyl, allyl, or hexenyl. Alternatively, each R 2 may be vinyl or hexenyl. Alternatively, each R 2 may be vinyl.
[0012] The starting material (A) is i) bis-vinyldimethylsiloxy terminated polydimethylsiloxane, ii) bis-vinyldimethylsiloxy terminated poly(dimethylsiloxane / methylvinylsiloxane); iii) bis-vinyldimethylsiloxy terminated polymethylvinylsiloxane; iv) bis-trimethylsiloxy terminated poly(dimethylsiloxane / methylvinylsiloxane); v) bis-trimethylsiloxy-terminated polymethylvinylsiloxane; vi) bis-hexenyldimethylsiloxy terminated polydimethylsiloxane; vii) bis-hexenyldimethylsiloxy terminated poly(dimethylsiloxane / methylhexenylsiloxane); viii) bis-hexenyldimethylsiloxy terminated polymethylhexenyl siloxane; ix) bis-trimethylsiloxy-terminated poly)dimethylsiloxane / methylhexenylsiloxane; x) bis-trimethylsiloxy-terminated polymethylhexenyl siloxane, xi) bis-hexenyldimethyl-siloxy terminated poly(dimethylsiloxane / methylvinylsiloxane); xii) bis-vinyldimethylsiloxy terminated poly(dimethylsiloxane / methylhexenylsiloxane); xii) is exemplified by a combination of two or more of i), ii), iii), iv), v), vi), vii), viii), ix), x), xi), and xii).
[0013] Methods for preparing alkenyl-containing polydialkylsiloxanes suitable for use as starting material (A), such as by hydrolysis and condensation of the corresponding organohalosilanes or equilibration of cyclic polydiorganosiloxanes, are well known in the art, see, for example, U.S. Pat. Nos. 3,284,406, 4,772,515, 5,169,920, 5,317,072, and 6,956,087.
[0014] The amount of (A) the first alkenyl-containing polydialkylsiloxane gum will vary depending on a variety of factors, such as the exact content of alkenyl groups in starting material (A), whether starting material (B) is present, and whether any other starting materials (e.g., (C) the alkenyl-containing polydialkylsiloxane polymer and / or the platinum group metal catalyst) contain alkenyl groups. However, the amount of starting material (A) may be at least 57 parts by weight, alternatively at least 60 parts by weight, alternatively at least 65 parts by weight, alternatively at least 70 parts by weight, alternatively at least 71 parts by weight, while the amount of starting material (A) may be up to 100 parts by weight, alternatively up to 90 parts by weight, alternatively up to 80 parts by weight, alternatively up to 75 parts by weight, alternatively up to 71 parts by weight.
[0015] (B) a second (higher) alkenyl-containing polydialkylsiloxane gum The starting material (B) in the pressure sensitive adhesive composition is a second alkenyl-containing polydialkylsiloxane gum that differs from the first alkenyl-containing polydiorganosiloxane gum at least in that it has a higher content of vinyl functionality. The second alkenyl-containing polydialkylsiloxane gum has silicon-bonded alkyl groups having 1 to 10 carbon atoms and silicon-bonded alkenyl groups having 2 to 6 carbon atoms. The vinyl functionality is present in an amount of 0.3% to 1.1% by weight based on the weight of the second alkenyl-containing polydialkylsiloxane gum. Alternatively, (A) the second alkenyl-containing polydialkylsiloxane gum may have 0.5% to 0.9% by weight of vinyl functionality.
[0016] The second alkenyl-containing polydialkylsiloxane gum of the starting material (B) has the unit formula (II): 1 2R 2 SiO 1 / 2 ) h (R 1 3SiO 1 / 2 ) i (R 1 R 2 SiO 2 / 2 ) j (R 1 2SiO 2 / 2 )k wherein each R 1 are independently an alkyl group of 1 to 10 carbon atoms as defined above, and each R 2 are independently an alkenyl group of 2 to 6 carbon atoms as defined above, and the subscripts h, i, j, and k represent the average number of each unit in the unit formula and have values such that 2≧h≧0, 2≧i≧0, 100≧j≧21, 10,000≧k≧2,000, and the amount (h+i)=2. Alternatively, in formula (II), the subscript j may be 50 to 150. Alternatively, the subscript k may be 5,000 to 7,000.
[0017] The starting material (B) is i) bis-vinyldimethylsiloxy terminated polydimethylsiloxane, ii) bis-vinyldimethylsiloxy terminated poly(dimethylsiloxane / methylvinylsiloxane); iii) bis-vinyldimethylsiloxy terminated polymethylvinylsiloxane; iv) bis-trimethylsiloxy terminated poly(dimethylsiloxane / methylvinylsiloxane); v) bis-trimethylsiloxy-terminated polymethylvinylsiloxane; vi) bis-hexenyldimethylsiloxy terminated polydimethylsiloxane; vii) bis-hexenyldimethylsiloxy terminated poly(dimethylsiloxane / methylhexenylsiloxane); viii) bis-hexenyldimethylsiloxy terminated polymethylhexenyl siloxane; ix) bis-trimethylsiloxy-terminated poly)dimethylsiloxane / methylhexenylsiloxane; x) bis-trimethylsiloxy-terminated polymethylhexenyl siloxane, xi) bis-hexenyldimethyl-siloxy terminated poly(dimethylsiloxane / methylvinylsiloxane); xii) bis-vinyldimethylsiloxy terminated poly(dimethylsiloxane / methylhexenylsiloxane); xii) is exemplified by a combination of two or more of i), ii), iii), iv), v), vi), vii), viii), ix), x), xi), and xii).
[0018] Methods for preparing alkenyl-containing polydialkylsiloxanes suitable for use as starting material (B), such as by hydrolysis and condensation of the corresponding organohalosilanes or equilibration of cyclic polydiorganosiloxanes, are well known in the art, see, for example, U.S. Pat. Nos. 3,284,406, 4,772,515, 5,169,920, 5,317,072, and 6,956,087.
[0019] The amount of (B) second alkenyl-containing polydialkylsiloxane gum will vary depending on a variety of factors, including the exact content of alkenyl groups in starting material (B), the amount and alkenyl content of starting material (A) present, and whether any other starting materials (e.g., platinum group metal catalysts) contain alkenyl groups. However, the amount of starting material (B) may be zero (since starting material (B) is optional). Alternatively, when (B) is present, the amount of (B) may be at least 25 parts by weight, alternatively at least 26 parts by weight, alternatively at least 27 parts by weight, alternatively at least 28 parts by weight, alternatively at least 29 parts by weight, while the amount of starting material (A) may be up to 43 parts by weight, alternatively at most 40 parts by weight, alternatively at most 35 parts by weight, alternatively at most 30 parts by weight, alternatively at most 29 parts by weight. The combined amount of starting materials (A) and (B) may total 100 parts by weight in the pressure-sensitive adhesive composition. The starting materials (A) and (B) are present in the pressure sensitive adhesive composition in an amount sufficient to provide a weight ratio, calculated by (B) / [(A)+(B)], of 0 to 0.5, alternatively 0 to 0.43, alternatively >0 to 0.5, alternatively >0 to 0.43, alternatively 0.25 to 0.43. Alternatively, the weight ratio (B) / [(A)+(B)] may be at least 0.25, alternatively at least 0.28, while the weight ratio (B) / [(A)+(B)] may be at most 0.5, alternatively at most 0.43, alternatively at most 0.29.
[0020] (C) Alkenyl-containing polydialkylsiloxane polymer The starting material (C) in the pressure sensitive adhesive composition is an alkenyl-containing polydialkylsiloxane polymer that differs from gums (A) and (B) at least in that it has a lower average number of siloxane units per molecule. The alkenyl-containing polydialkylsiloxane polymer has silicon-bonded alkyl groups having 1 to 10 carbon atoms and silicon-bonded alkenyl groups having 2 to 6 carbon atoms. The vinyl functionality is present in an amount of 0.01% to 2% by weight based on the weight of the alkenyl-containing polydialkylsiloxane polymer.
[0021] The second alkenyl-containing polydialkylsiloxane polymer of the starting material (C) has the unit formula (III): 1 2R 2 SiO 1 / 2 ) r (R 1 3SiO 1 / 2 ) m (R 1 R 2 SiO 2 / 2 ) n (R 1 2SiO 2 / 2 ) o wherein each R 1 are independently an alkyl group of 1 to 10 carbon atoms as defined above, and each R 2 are independently alkenyl groups of 2 to 6 carbon atoms as described above, and the subscripts i, m, n, and o represent the average number of each unit in the unit formula and have values such that 2≧r≧0, 2≧m≧0, 100≧n≧0, 1,000≧o≧10, and the amount (r+m)=2. Alternatively, in unit formula (III), the subscript r may be 2 and the subscript m may be 0. Alternatively, the subscript o may be 400 to 1,000, or alternatively, 450 to 950. Alternatively, the subscript n may be 0.
[0022] The starting material (C) is i) bis-vinyldimethylsiloxy terminated polydimethylsiloxane, ii) bis-vinyldimethylsiloxy terminated poly(dimethylsiloxane / methylvinylsiloxane); iii) bis-vinyldimethylsiloxy terminated polymethylvinylsiloxane; iv) bis-trimethylsiloxy terminated poly(dimethylsiloxane / methylvinylsiloxane); v) bis-trimethylsiloxy-terminated polymethylvinylsiloxane; vi) bis-hexenyldimethylsiloxy terminated polydimethylsiloxane; vii) bis-hexenyldimethylsiloxy terminated poly(dimethylsiloxane / methylhexenylsiloxane); viii) bis-hexenyldimethylsiloxy terminated polymethylhexenyl siloxane; ix) bis-trimethylsiloxy-terminated poly)dimethylsiloxane / methylhexenylsiloxane; x) bis-trimethylsiloxy-terminated polymethylhexenyl siloxane, xi) bis-hexenyldimethyl-siloxy terminated poly(dimethylsiloxane / methylvinylsiloxane); xii) bis-vinyldimethylsiloxy terminated poly(dimethylsiloxane / methylhexenylsiloxane); xii) is exemplified by a combination of two or more of i), ii), iii), iv), v), vi), vii), viii), ix), x), xi), and xii).
[0023] Methods for preparing alkenyl-containing polydialkylsiloxanes suitable for use as starting material (B), such as by hydrolysis and condensation of the corresponding organohalosilanes or equilibration of cyclic polydiorganosiloxanes, are well known in the art, see, for example, U.S. Pat. Nos. 3,284,406, 4,772,515, 5,169,920, 5,317,072, and 6,956,087.
[0024] The amount of (C) alkenyl-containing polydialkylsiloxane polymer will vary depending on a variety of factors, such as the exact content of alkenyl groups in starting material (C), the amount and alkenyl content of starting material (A) present, whether starting material (B) is present, and whether any other starting materials (e.g., platinum group metal catalysts) contain alkenyl groups. However, the amount of starting material (C) may be 0 (since starting material (C) is optional). Alternatively, when (C) is present, the amount of (C) may be >0 parts by weight, alternatively at least 75 parts by weight, alternatively at least 80 parts by weight, alternatively at least 81 parts by weight, alternatively at least 82 parts by weight, alternatively at least 83 parts by weight, while the amount of starting material (C) may be up to 143 parts by weight, alternatively at most 140 parts by weight, alternatively at most 135 parts by weight, alternatively at most 130 parts by weight, alternatively at most 125 parts by weight. The amounts of starting materials (A), (B), and (C) may be such that the weight ratio calculated by [(A)+(B)] / (C) is at least 0.5, alternatively at least 0.6, alternatively at least 0.7, alternatively at least 1.2, while the weight ratio calculated by [(A)+(B)] / (C) may be at most 2.5, alternatively at most 1.5, alternatively at most 1.3.
[0025] (D) Polyalkylhydrogensiloxane The starting material (D) in the pressure-sensitive adhesive composition is a polyalkylhydrogensiloxane having silicon-bonded alkyl groups having from 1 to 10 carbon atoms, at least 3 silicon-bonded hydrogen atoms per molecule, and an average of at least 1 weight percent silicon-bonded hydrogen atoms.
[0026] The starting material (D) polyalkylhydrogensiloxane has the unit formula (IV): 1 3SiO 1 / 2 )3(R 1 2SiO 2 / 2 ) p (R 1 HSiO 2 / 2 ) q wherein each R 1are independently an alkyl group of 1 to 10 carbon atoms as defined above, and the subscripts p and q represent the average number of each difunctional unit in the unit formula and have values such that 0≦p≦2,000 and 2≦q≦2000. Alternatively, the subscript p may be 0. Alternatively, the subscript q may be 15 to 50, alternatively 20 to 45, alternatively 25 to 40, alternatively 30 to 35.
[0027] The polyalkylhydrogensiloxane for the starting material (D) is a) bis-dimethylhydrogensiloxy terminated poly(dimethylsiloxane / methylhydrogensiloxane); b) bis-dimethylhydrogensiloxy terminated polymethylhydrogensiloxane; c) bis-trimethylsiloxy terminated poly(dimethylsiloxane / methylhydrogensiloxane); d) bis-trimethylsiloxy-terminated polymethylhydrogensiloxane, and e) exemplified by a combination of two or more of a), b), c), and d).
[0028] Methods for preparing linear, branched, and cyclic polyalkylhydrogensiloxanes suitable for use as starting material (D), such as the hydrolysis and condensation of alkylhalosilanes, are known in the art, as exemplified by U.S. Pat. No. 2,823,218 to Speier, U.S. Pat. No. 3,957,713 to Jeram et al., and U.S. Pat. No. 4,329,273 to Hardman et al.
[0029] The amount of (D) polyalkylhydrogensiloxane polymer will vary depending on a variety of factors, such as the alkenyl content and amount of starting materials (A), (B), and (C) present, and whether any other starting materials (e.g., platinum group metal catalyst) contain alkenyl groups. However, the amount of starting material (D) may be sufficient for the silicone pressure sensitive adhesive composition to have an overall SiH / Vi ratio, i.e., starting materials in the composition that combine to provide a molar ratio of silicon-bonded hydrogen atoms (SiH) / silicon-bonded alkenyl groups (Vi) of 3.3 to 5.21, alternatively 3.8 to 5.1, alternatively 4.1 to 4.8, alternatively 4.2 to 4.3. Alternatively, the overall SiH / Vi ratio may be at least 3.33, alternatively at least 3.8, alternatively at least 4.0, alternatively at least 4.1, alternatively at least 4.2, while the overall SiH / Vi ratio may be up to 5.21, alternatively up to 5.1, alternatively up to 5.0, alternatively up to 4.8, alternatively up to 4.5, alternatively up to 4.3. Alternatively, the polyalkylhydrogensiloxane may be present in the pressure sensitive adhesive composition in an amount of from 4 parts by weight to 10 parts by weight.
[0030] (E) Platinum group metal catalyst The pressure-sensitive adhesive composition further comprises a platinum group metal catalyst capable of catalyzing hydrosilylation. Suitable platinum group metal catalysts are known in the art and commercially available. The catalyst may be a platinum group metal selected from platinum, rhodium, ruthenium, palladium, osmium, and iridium. Alternatively, the catalyst may be a compound of such a metal (e.g., chloroplatinic acid, chloroplatinic acid hexahydrate, platinum dichloride), and a complex of the compound with an alkenyl-functional organopolysiloxane, or a platinum compound microencapsulated in a matrix or core / shell structure. Complexes of platinum with an alkenyl-functional organopolysiloxane include 1,3-diethenyl-1,1,3,3-tetramethyldisiloxane platinum complex. These complexes may be microencapsulated in a resin matrix. Exemplary hydrosilylation catalysts are described in U.S. Patent Nos. 3,159,601, 3,220,972, 3,296,291, 3,419,593, 3,516,946, 3,814,730, 3,989,668, 4,784,879, 5,036,117, and 5,175,325, and in European Patent No. 0347895(B). Microencapsulated hydrosilylation catalysts and methods for their preparation are known in the art, as exemplified in U.S. Patent Nos. 4,766,176 and 5,017,654.
[0031] The catalyst is added to the pressure-sensitive adhesive composition in an amount sufficient to catalyze the hydrosilylation reaction, typically to provide from 10 ppm to 5,000 ppm by weight of platinum group metal, based on the total weight of all starting materials in the pressure-sensitive adhesive composition excluding solvent. Alternatively, when the platinum group metal catalyst comprises a compound or complex of platinum and an alkenyl-functional organopolysiloxane, such as 1,3-diethenyl-1,1,3,3-tetramethyldisiloxane platinum complex, the amount may be from 5 parts by weight to 10 parts by weight, or alternatively from 6 parts by weight to 7.5 parts by weight.
[0032] (F) Acetylenic alcohol The pressure-sensitive adhesive composition further comprises an acetylenic alcohol. The acetylenic alcohol can be added as an inhibitor or stabilizer of the pressure-sensitive adhesive composition. Suitable acetylenic alcohols are exemplified by methylbutynol, ethynylcyclohexanol (ETCH), dimethylhexynol, and 3,5-dimethyl-1-hexyn-3-ol, 1-butyn-3-ol, 1-propyn-3-ol, 2-methyl-3-butyn-2-ol, 3-methyl-1-butyn-3-ol, 3-methyl-1-pentyn-3-ol, 3-phenyl-1-butyn-3-ol, 4-ethyl-1-octyn-3-ol, 3,5-dimethyl-1-hexyn-3-ol, and 1-ethynyl-1-cyclohexanol, and combinations thereof. Alternatively, the starting material (F) may be selected from the group consisting of (F-1) 1-ethynyl-1-cyclohexanol, (F-2) methylbutynol, (F-3) diallyl maleate, and (F-4) a combination of two or more of (F-1), (F-2) and (F-3). Alternatively, the starting material (F) is exemplified by ETCH. Acetylenic alcohols are commercially available from various sources, such as Sigma-Aldrich, Inc. (St. Louis, Missouri, USA).
[0033] The amount of acetylenic alcohol added to the composition will vary depending on a variety of factors, including the desired pot life of the pressure sensitive adhesive composition, whether the composition is a one-part or multi-part composition, the particular acetylenic alcohol used, and the amount of polyalkylhydrogensiloxane. However, when present, the amount of starting material (F) can be from 0.01 to 0.5 parts by weight.
[0034] (G) Fixing additives The pressure-sensitive adhesive composition may optionally include an anchoring additive.Without being bound by theory, it is believed that the anchoring additive promotes the bonding of the pressure-sensitive adhesive prepared by curing the pressure-sensitive adhesive composition described herein to the substrate.However, the presence of the anchoring additive does not adversely affect the desired peel force, thereby allowing the pressure-sensitive adhesive to be removed from electronic devices, such as fragile layers in OLEDs, without damaging the device or leaving significant residue.
[0035] Suitable fixing additives include silane coupling agents such as methyltrimethoxysilane, vinyltrimethoxysilane, allyltrimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, bis(trimethoxysilyl)propane, and bis(trimethoxysilyl)hexane, as well as mixtures or reaction mixtures of such silane coupling agents. Alternatively, the fixing additive can be tetramethoxysilane, tetraethoxysilane, dimethyldimethoxysilane, methylphenyldimethoxysilane, methylphenyldiethoxysilane, phenyltrimethoxysilane, methyltrimethoxysilane, methyltriethoxysilane, vinyltriethoxysilane, allyltriethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, -(3,4-epoxycyclohexyl)ethyltrimethoxysilane, or 3-methacryloxypropyltrimethoxysilane.
[0036] Alternatively, exemplary adhesion promoters may include reaction products of alkenyl-functional alkoxysilanes (e.g., vinyl alkoxysilanes) with epoxy-functional alkoxysilanes, reaction products of alkenyl-functional acetoxysilanes (e.g., vinyl acetoxysilanes) with epoxy-functional alkoxysilanes, and combinations (e.g., as physical blends and / or reaction products) of polyorganosiloxanes having at least one aliphatically unsaturated hydrocarbon group and at least one hydrolyzable group per molecule with epoxy-functional alkoxysilanes (e.g., a combination of a hydroxy-terminated vinyl-functional polydimethylsiloxane with glycidoxypropyltrimethoxysilane). Suitable solid additives and methods for their preparation are disclosed, for example, in U.S. Pat. No. 9,562,149, U.S. Patent Application Publication Nos. 2003 / 0088042, 2004 / 0254274, 2005 / 0038188, 2012 / 0328863, paragraph
[0091] , and U.S. Patent Application Publication No. 2017 / 0233612, paragraph
[0041] , and European Patent No. 0556023.
[0037] Fixation additives are commercially available. For example, SYL-OFF™ 297, SYL-OFF™ 397, and SYL-OFF™ 9176 are available from Dow Silicones Corporation (Midland, Michigan, USA). Other exemplary fixation additives include (G-1) vinyltriacetoxysilane, (G-2) glycidoxypropyltrimethoxysilane, (G-3) 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, (G-4) a combination of two or more of (G-1), (G-2), and (G-3), and (G-5) a combination of any of (G-1), (G-2), (G-3), and / or (G-4) with a polydimethylsiloxane terminated with hydroxyl groups, methoxy groups, or both hydroxyl and methoxy groups. The combination of (G-4) and (G-5) can be a physical blend and / or a reaction product.
[0038] The amount of the adhesion promoter will vary depending on a variety of factors, including the type of substrate to which the composition is applied and whether a primer or other surface treatment is used prior to application of the composition, however, the amount of adhesion promoter may be from 0 to 5 parts by weight, alternatively from 1 to 5 parts by weight.
[0039] (H) Organic Solvent The pressure-sensitive adhesive composition further comprises a solvent. The solvent can be an organic solvent. The organic solvent can be an alcohol such as methanol, ethanol, isopropanol, butanol, or n-propanol; a ketone such as acetone, methyl ethyl ketone, or methyl isobutyl ketone; an aromatic hydrocarbon such as benzene, toluene, or xylene; an aliphatic hydrocarbon such as heptane, hexane, or octane; a glycol ether such as propylene glycol methyl ether, dipropylene glycol methyl ether, propylene glycol n-butyl ether, propylene glycol n-propyl ether, or ethylene glycol n-butyl ether, a halogenated hydrocarbon, for example, dichloromethane, 1,1,1-trichloroethane, or methylene chloride; chloroform; dimethyl sulfoxide; dimethylformamide, acetonitrile; tetrahydrofuran, white spirit; mineral spirit; naphtha; n-methylpyrrolidone; or a combination thereof. Alternatively, the solvent can be selected from the group consisting of benzene, toluene, ethylbenzene, xylene, and combinations of two or more thereof.
[0040] The amount of solvent varies depending on a variety of factors, including the type of solvent selected and the amount and type of other starting materials selected for the pressure-sensitive adhesive composition. However, the amount of solvent may range from 10% to 90%, alternatively 20% to 60%, based on the total weight of all starting materials in the pressure-sensitive adhesive composition. The solvent may be added during preparation of the pressure-sensitive adhesive composition, for example, to aid in mixing and delivery. All or a portion of the solvent may be added with one of the other starting materials. For example, one or more of the gum, polymer, and catalyst may be dissolved in a solvent, such as an aromatic hydrocarbon or alcohol, before combining with the other starting materials in the composition. All or a portion of the solvent may optionally be removed after preparing the pressure-sensitive adhesive composition.
[0041] When selecting starting materials for the pressure sensitive adhesive composition described above, certain starting materials described herein may have multiple functions and therefore overlap between types of starting materials. For example, certain alkoxysilanes may be useful as adhesion promoters and anchoring additives. When additional starting materials are added to the composition, the additional starting materials are different from each other and different from the starting materials required for the composition.
[0042] The pressure-sensitive adhesive composition may be free of silicone resins, such as polyorganosilicate resins and / or silsesquioxane resins. As used herein, "free of silicone resins" means that the pressure-sensitive adhesive composition contains an undetectable amount of silicone resin, or contains an amount of silicone resin that does not change the properties measured according to Example 2 below, compared to the same composition without the silicone resin.
[0043] The pressure-sensitive adhesive composition may be free of fillers or may contain only limited amounts of fillers, such as 0-30% based on the total weight of all starting materials in the composition. Without being bound by theory, it is believed that fillers may clump or otherwise stick to the equipment used to apply or dispense the pressure-sensitive adhesive composition, and fillers may inhibit the optical properties, such as transparency, of the pressure-sensitive adhesive composition and silicone pressure-sensitive adhesive films formed therewith, if optical clarity is desired. Fillers may also adversely affect the adhesion of the silicone pressure-sensitive adhesive film to the substrate.
[0044] The pressure sensitive adhesive composition can be prepared by a process that includes combining all of the starting materials by any convenient means, such as mixing at ambient or elevated temperature. For example, when the pressure sensitive adhesive composition is prepared at elevated temperature and / or when the pressure sensitive adhesive composition is prepared as a one-part composition, the acetylenic alcohol can be added before the platinum group metal catalyst.
[0045] Alternatively, the pressure-sensitive composition can be prepared as a multi-part composition, for example when the composition is stored for a long period of time before use.In the multi-part composition, the platinum group metal catalyst is stored in a separate part from any starting material having silicon-bonded hydrogen atoms, such as polyalkyl hydrogen siloxane, and the parts are combined immediately before the use of the pressure-sensitive adhesive composition.For example, the two-part composition can be prepared by combining starting materials including a first alkenyl-containing polydialkyl siloxane gum, a second alkenyl-containing polydialkyl siloxane gum, and one or more of alkenyl-containing polydialkyl siloxane polymers; polyalkyl hydrogen siloxanes; and organic solvents, and optionally one or more of the above-mentioned other additional starting materials by any convenient means, such as mixing, to form a base. The curing agent may be prepared by combining starting materials including one or more of the first alkenyl-containing polydialkylsiloxane gum, the second alkenyl-containing polydialkylsiloxane gum, and the alkenyl-containing polydialkylsiloxane polymer; a platinum group metal catalyst; and an organic solvent, and optionally one or more other additional starting materials described above, by any convenient means, such as mixing. The starting materials may be mixed at ambient or elevated temperature. The acetylenic alcohol may be included in one or more of the base, the hardener, or a separate additional part. The adhesion promoter may be added to the base or may be added as a separate additional part. When a two-part composition is used, the weight ratio of the amount of base to the amount of hardener may range from 1:1 to 10:1. The pressure-sensitive adhesive composition cures by a hydrosilylation reaction to form a pressure-sensitive adhesive.
[0046] The above method may further include one or more additional steps. The pressure-sensitive adhesive composition prepared as above may be used to form an adhesive article, such as a pressure-sensitive adhesive (prepared by curing the pressure-sensitive adhesive composition) on a substrate. The above method may further include applying the pressure-sensitive adhesive curing composition to a substrate.
[0047] Applying the pressure-sensitive adhesive curing composition to the substrate can be carried out by any convenient means. For example, the pressure-sensitive adhesive curing composition can be applied onto the substrate by a gravure coater, an offset coater, an offset gravure coater, a roller coater, a reverse roller coater, an air knife coater, or a curtain coater.
[0048] The substrate can be any material that can withstand the curing conditions (described below) used to cure the pressure-sensitive adhesive curable composition to form a pressure-sensitive adhesive on the substrate. For example, any substrate that can withstand heat treatment at a temperature of 120°C or higher, or even 150°C, is suitable. Examples of materials suitable for such substrates include plastic films such as polyimide (PI), polyetheretherketone (PEEK), polyethylenenaphthalate (PEN), liquid crystal polyarylate, polyamideimide (PAI), polyethersulfide (PES), or polyethyleneterephthalate (PET), or PE (polyethylene), or PP (polypropylene). Alternatively, the substrate can be a metal foil such as aluminum foil or copper foil. The thickness of the substrate is not critical. However, the thickness may range from 5 micrometers to 300 micrometers.
[0049] To improve bonding of the pressure-sensitive adhesive to the substrate, the method may optionally further comprise treating the substrate prior to applying the pressure-sensitive adhesive composition. Treatment of the substrate may be carried out by any convenient means, such as applying a primer or subjecting the substrate to a corona discharge treatment, etching, or plasma treatment prior to applying the pressure-sensitive adhesive composition to the substrate.
[0050] Adhesive articles such as protective films can be prepared by applying the pressure-sensitive adhesive composition described above onto the substrate described above. The method may optionally further comprise removing all or a portion of the solvent before and / or during curing. Removal of the solvent may be carried out by any convenient technique, such as by heating the pressure-sensitive adhesive composition at a temperature that vaporizes the solvent without completely curing it, for example at a temperature of 70°C to 120°C, alternatively 50°C to 100°C, alternatively 70°C to 80°C, for a time sufficient to remove all or a portion of the solvent (e.g., 30 seconds to 1 hour, alternatively 1 minute to 5 minutes).
[0051] The method then further comprises curing the pressure-sensitive adhesive composition (which may have had some or all of the solvent removed when the drying step is performed) by heating at room temperature or at a temperature of 140°C to 220°C, alternatively 150°C to 220°C, alternatively 160°C to 200°C, alternatively 165°C to 180°C, for a time sufficient to cure the pressure-sensitive adhesive curable composition (e.g., 30 seconds to 1 hour, alternatively 1 minute to 5 minutes). This forms a pressure-sensitive adhesive film on the substrate. Drying and / or curing can be performed by placing the substrate in an oven. The amount of pressure-sensitive adhesive composition applied to the substrate will vary depending on the particular application, but the amount can be sufficient that the thickness of the pressure-sensitive adhesive after curing can be from 5 micrometers to 200 micrometers, and in the case of a protective film, the thickness can be from 10 micrometers to 50 micrometers, alternatively 20 micrometers to 40 micrometers, alternatively 30 micrometers.
[0052] The methods described herein may optionally further include applying a removable release liner to a surface of the pressure-sensitive adhesive film opposite the substrate, for example, to protect the pressure-sensitive adhesive prior to use of the adhesive article.
[0053] The adhesive article (eg, protective film) prepared as described above is suitable for use in flexible OLED device fabrication processes as a protective film with low adhesion, high adhesion stability, and / or low migration.
[0054] For example, a method of making a flexible OLED device can include forming an OLED module on a surface of a substrate, e.g., a fragile layer such as a thin film encapsulating layer or a passivation layer on a surface of the OLED module opposite the substrate, and applying a protective film prepared as described herein to the surface of the fragile layer on the opposite side of the OLED module. EXAMPLES
[0055] These examples are intended to illustrate some embodiments of the invention and should not be construed as limiting the scope of the invention as set forth in the claims. The starting materials used in these examples are listed in Table 1. [Table 1]
[0056] Example 1. Preparation of Pressure Sensitive Adhesive Composition Samples The general procedure for preparing the pressure-sensitive adhesive composition samples is as follows: To prepare the sample labeled Ex.1 (Example 1), a solution was prepared by mixing the following starting materials in a mixer: First, 100 g of starting material (A1) was dissolved in 330 g of toluene (H). Then, 83.3 g of starting material (C1), 4.17 g of starting material (D1), 0.07 g of starting material (F1), and starting material (G1) were added. After mixing the starting materials, the resulting solution was further mixed with 6.25 g of starting material (E1). A silicone pressure-sensitive adhesive composition was made by mixing the starting materials with the aforementioned solution. This composition was used to fabricate adhesive tapes. Comparative Examples 1-23 and Examples 2-9 were similarly prepared using the starting materials and amounts in the table.
[0057] Example 2. Analysis of Pressure Sensitive Adhesives In this Example 2A, the adhesion measurement was carried out as follows: the silicone pressure-sensitive adhesive composition prepared as above was applied onto a polyethylene terephthalate (PET, 75 μm) film, and after curing, a silicone pressure-sensitive adhesive layer was formed with a thickness of 75 μm. A silicone pressure-sensitive adhesive tape was made by heating the film at 150° C. for 2 minutes. The resulting pressure-sensitive adhesive tape was applied onto a peelable polyethylene terephthalate film using a laminator, and the resulting laminate was aged at room temperature for 1 day. The resulting sheet was cut into tape strips with a width of 2.54 cm (1 inch), and after removing the peelable polyethylene terephthalate film, the tape strip was placed on a glass plate and bonded to it by moving a rubber-covered pressure roller with a weight of 2 kg back and forth over the strip twice. The assembly was kept at room temperature for 1 hour. The adhesion force (gf / inch) was measured by peeling the tape from the glass plate by pulling at a speed of 2400 mm / min and an angle of 180°. To examine the increase in adhesive strength during storage, assemblies prepared as described above were stored at room temperature for 3 days, and the adhesive strength was then measured in the same manner.
[0058] In this Example 2B, the residual adhesive-residual properties and silicone-transferability-residual adhesion rate (%) were evaluated as follows: A pressure-sensitive adhesive tape (prepared according to Example 2A above) was cut into a tape strip 2.54 cm (1 inch) wide, which was placed on a glass plate after removing the peelable polyethylene terephthalate film, and a rubber-coated pressure roller weighing 2 kg was bonded to it by moving it back and forth twice over the strip. After aging the sample at 50°C for 3 days, the resulting tape was removed from the glass plate. Then, TESA® 7475 tape was adhered by a 2 kg roller to the place where the tape was removed. After 30 minutes, the adhesion was measured by peeling TESA® 7475 from the substrate at an angle of 180° to the substrate surface using a tensile tester with a constant speed of 300 mm / min. For reference, TESA® 7475 tape was adhered to glass, and adhesion was measured by the same method. The degree of migration, referred to as percent residual adhesion, was calculated from the following formula; percent residual adhesion=[test sample adhesion, gf / inch] / [reference sample adhesion, gf / inch].
[0059] In this Example 2C, scratch resistance was measured as follows: For pressure-sensitive adhesive tapes prepared in the same manner as in Example 2A, the occurrence of surface scratches and the restoration of scratches (scratches) were observed on the surface layer of the film using a copper brush. In Tables 2 to 7, PASS (PASS) means that the sample was not scratched. NG means that the sample was scratched.
[0060] In this Example 2D, the recovery property was measured as follows: for the pressure-sensitive adhesive tape prepared in the same manner as in Example 2A, a stylus pen was used to write strongly on the film surface layer, and then an indentation was observed. PASS means that the sample instantly recovered within 10 seconds, so no indentation was observed. NG means that the sample did not recover, so an indentation was observed. [Table 2] [Table 3] [Table 4] [Table 5] [Table 6] [Table 7] [Industrial Applicability]
[0061] During the fabrication of OLED devices, weak or brittle layers need to be protected from damage (e.g., scratches or other impacts) using protective films. There is a need in the industry to provide protective films that have low adhesion and high adhesion stability when the protective film is removed after use (wherein the adhesion does not increase during the time required for the fabrication process to a degree that would cause delamination or damage).
[0062] It is also important to keep the surface of the layer clean so that additional films or layers can be laminated after the protective film is removed.Therefore, there is a need in the industry to provide protective films with low migration properties (so that no or minimal adhesive from the protective film remains on the surface of the layer of the flexible OLED device after the protective film is removed).
[0063] Since the protective film is exposed to various process conditions (pressure and temperature) during the fabrication of an OLED device, the protective film may be deformed and / or scratched by mechanical stress. Therefore, it is also desirable for the protective film to have scratch resistance and recovery against such mechanical stress.
[0064] The pressure-sensitive adhesive composition described herein is cured to form a pressure-sensitive adhesive suitable for use in protective films for OLED device fabrication processes. The pressure-sensitive adhesive can exhibit 1) very low adhesion, 2) adhesion stability during aging, 3) low migration, 4) scratch resistance, and 5) recovery, as evaluated above according to the test method of Example 2. The above examples show that the pressure-sensitive adhesive prepared by curing the pressure-sensitive adhesive composition described above can have very low adhesion (when tested according to Example 2A) indicated by adhesion of <3 gf / inch on glass; good adhesion stability (when tested according to Example 2A) indicated by adhesion increase of ≦6 gf / inch on glass; low migration indicated by residual adhesion of >50% as calculated in Example 2B; scratch resistance that passes when tested according to Example 2C; and recovery that passes when tested according to Example 2D. Without being bound by theory, these properties when tested on glass are believed to provide results that are comparable to weak or brittle substrates used in OLED fabrication processes, such as fragile layers, and it is predicted that this combination of properties will enable the pressure sensitive adhesive film to be used as a protective film over fragile layers during the fabrication of flexible OLED devices.
[0065] Test Method The alkenyl content of the alkenyl-containing siloxanes described herein, e.g., starting materials (A), (B), and (C), can be calculated by calculating the total molecular weight of the siloxane, calculating the molecular weight of each unit containing an alkenyl group, and dividing the sum of the molecular weights of each unit containing an alkenyl group by the total molecular weight. For example, in the formula (R 1 2R 2 SiO 1 / 2 ) d (R 1 3SiO 1 / 2 ) e (R 1 R2SiO 2 / 2 ) f (R 1 2SiO 2 / 2 ) g In R 1 is methyl and R2 is vinyl, subscript d=2, subscript e=0, subscript f=11.3, and subscript g=7084, then the siloxane is dimethylvinylsiloxy-terminated poly(dimethylsiloxane / methylvinylsiloxane) copolymer (M Vi 2D Vi 11.3 D 4829 ) where the number average molecular weight (Mn) and alkenyl (vinyl) content are calculated as follows: The number average molecular weight of the copolymer is 526,439 g / mol. M Vi Mw=93.20g / mol, Mw=74.15g / mol and D Vi In the case of Mw=86.17g / mol, →M Vi D 7084 D Vi 11.3 M Vi Mn=2*93.2+7084*74.15+11.3*86.17=526,439g / mol, Vinyl content = 0.07% M Vi Mw=93.20g / mol, D Mw=74.15g / mol, D vi Mw=86.17g / mol and Mw=27 for vinyl. →M Vi D 7084 D Vi 11.3 M Vi Mn=[(2*27)+(11.3*27)] / [(2*93.2+7084*74.15+11.3*86.17)]*100%=0.07%.
[0066] The silicon-bonded hydrogen (SiH) content of the polyalkylhydrogensiloxanes described herein may be determined using quantitative infrared analysis in accordance with ASTM E168.
[0067] The silicon-bonded hydrogen to alkenyl (e.g., vinyl) ratio (i.e., SiH / Vi ratio) is important when relying on a hydrosilylation reaction curing process. Generally, this is determined by calculating the total weight percent of alkenyl groups, e.g., vinyl [Vi], in the composition and the total weight percent of silicon-bonded hydrogen [SiH] in the composition, where the molecular weight of hydrogen is 1 and the molecular weight of vinyl (CH2=CH-) is 27, the molar ratio of silicon-bonded hydrogen to vinyl is 27*[SiH] / [Vi]. Starting materials (A), (B), (C), (D), and any other starting materials containing the above SiH and / or vinyl content, as described above, may be selected to provide a SiH / Vi ratio of 3.3 to 5.21, as described above.
[0068] Use of the term All amounts, ratios, and percentages are by weight unless the context of the specification dictates otherwise. The articles "a," "an," and "the" each refer to one or more, unless the context of the specification dictates otherwise. The disclosure of a range includes the range itself and any subsumed within the range, as well as the endpoints. For example, the disclosure of a range of 0.7 to 1.2 includes not only the range 0.7 to 1.2, but also individually 0.7, 0.8, 0.85, 0.9, 1, 1.1, and 1.2, and any other numbers subsumed within that range. Further, for example, the disclosure of a range of 0.7 to 1.2 includes the subsets 0.7 to 0.85, 0.9 to 1.05, and 1.05 to 1.2, as well as any other subset subsumed within that range. Similarly, the disclosure of a Markush group includes the group as a whole, as well as any individual elements and subgroups subsumed therein. For example, disclosure of a Markush group of vinyl, allyl, or hexenyl includes individually the member vinyl; the subgroups vinyl and hexenyl; and any other individual members and subgroups subsumed therein.
[0069] The abbreviations used herein have the meanings set out in Table 8 below. [Table 8]
[0070] EMBODIMENTS OF THE PRESENT DISCLOSURE In a first embodiment, a method of fabricating a flexible organic light emitting diode device includes: 1) applying a pressure sensitive adhesive composition to a surface of a substrate; 2) curing the pressure-sensitive adhesive composition to form a pressure-sensitive adhesive film; and 3) applying a pressure sensitive adhesive film to a fragile layer within the device; and the pressure sensitive adhesive composition comprises (A) a first alkenyl-containing polydialkylsiloxane gum having silicon-bonded alkyl groups having 1 to 10 carbon atoms and silicon-bonded alkenyl groups having 2 to 6 carbon atoms, the vinyl functionality being present in an amount of 0.03% to 0.11% by weight, based on the weight of the first alkenyl-containing polydialkylsiloxane gum; optionally, (B) a second alkenyl-containing polydialkylsiloxane gum having silicon-bonded alkyl groups having 1 to 10 carbon atoms and silicon-bonded alkenyl groups having 2 to 6 carbon atoms, the vinyl functionality being present in an amount of 0.3% to 1.1% by weight, based on the weight of the second alkenyl-containing polydialkylsiloxane gum; wherein starting materials (A) and (B) are present in amounts sufficient to provide a weight ratio, calculated by (B) / [(A)+(B)], of 0 to 0.5; (C) an alkenyl-containing polydialkylsiloxane polymer having silicon-bonded alkyl groups having 1 to 10 carbon atoms and silicon-bonded alkenyl groups having 2 to 6 carbon atoms, the vinyl functionality being present in an amount of 0.01% to 2% by weight based on the weight of the alkenyl-containing polydialkylsiloxane polymer; wherein starting materials (A), (B), and (C) are present in amounts to provide a weight ratio calculated by [(A)+(B)] / (C)] of 0.5 to 2.5; (D) a polyalkylhydrogensiloxane having a silicon-bonded alkyl group having from 1 to 10 carbon atoms, at least 3 silicon-bonded hydrogen atoms per molecule, and an average of at least 1 weight percent silicon-bonded hydrogen atoms; (E) a platinum group metal catalyst in an amount sufficient to provide a Pt-group metal concentration in the composition of from 10 to 5000 ppm by weight; (F) an acetylenic alcohol; optionally, (G) an adhesion promoter; and (H) 10% to 90% by weight of an organic solvent, based on the total weight of all starting materials in the composition; provided that all of the starting materials in the combined composition have a molar ratio of silicon-bonded hydrogen atoms to silicon-bonded alkenyl groups (SiH / Vi ratio) of from 3.33 to 5.21.
[0071] In a second embodiment, a method of fabricating a flexible organic light emitting diode device includes applying a pressure sensitive adhesive film to a fragile layer or thin film encapsulation layer in the device, the pressure sensitive adhesive film comprising: (A) a first alkenyl-containing polydialkylsiloxane gum having silicon-bonded alkyl groups having 1 to 10 carbon atoms and silicon-bonded alkenyl groups having 2 to 6 carbon atoms, the vinyl functionality being present in an amount of 0.03% to 0.11% by weight, based on the weight of the first alkenyl-containing polydialkylsiloxane gum; optionally, (B) a second alkenyl-containing polydialkylsiloxane gum having silicon-bonded alkyl groups having 1 to 10 carbon atoms and silicon-bonded alkenyl groups having 2 to 6 carbon atoms, the vinyl functionality being present in an amount of 0.3% to 1.1% by weight, based on the weight of the second alkenyl-containing polydialkylsiloxane gum; wherein starting materials (A) and (B) are present in amounts sufficient to provide a weight ratio, calculated by (B) / [(A)+(B)], of 0 to 0.5; (C) an alkenyl-containing polydialkylsiloxane polymer having silicon-bonded alkyl groups having 1 to 10 carbon atoms and silicon-bonded alkenyl groups having 2 to 6 carbon atoms, the vinyl functionality being present in an amount of 0.01% to 2% by weight based on the weight of the alkenyl-containing polydialkylsiloxane polymer; (wherein the starting materials (A), (B), and (C) are present in amounts to provide a weight ratio, calculated by [(A)+(B)] / (C), of 0.6 to 1.5; (D) a polyalkylhydrogensiloxane having a silicon-bonded alkyl group having from 1 to 10 carbon atoms, at least 3 silicon-bonded hydrogen atoms per molecule, and an average of at least 1 weight percent silicon-bonded hydrogen atoms; (E) a platinum group metal catalyst in an amount sufficient to provide a Pt-group metal concentration in the composition of from 10 to 5000 ppm by weight; (F) an acetylenic alcohol; optionally, (G) an adhesion promoter; and (H) 10% to 90% by weight of an organic solvent, based on the total weight of all starting materials in the composition; provided that all of the starting materials in the combined composition have a molar ratio of silicon-bonded hydrogen atoms to silicon-bonded alkenyl groups (SiH / Vi ratio) of from 3.33 to 5.21.
[0072] In a third embodiment, in the method of the first or second embodiment, (A) the first alkenyl-containing polydialkylsiloxane gum is a polydialkylsiloxane having a unit formula (I): (R 1 2R 2 SiO 1 / 2 ) d (R 1 3SiO 1 / 2 ) e (R 1 R 2 SiO 2 / 2 ) f (R 1 2SiO 2 / 2 ) g wherein each R 1are independently an alkyl group of 1 to 10 carbon atoms, and each R 2 are independently alkenyl groups of 2 to 6 carbon atoms, and the subscripts d, e, f, and g represent the average number of each unit in the unit formula and have values such that 2≧d≧0, 2≧e≧0, 20≧f≧5, 10,000≧g≧2,000, and the amount (d+e)=2.
[0073] In a fourth embodiment, in the method of the first or second embodiment, (A) the first alkenyl-containing polydialkylsiloxane gum has 0.05% to 0.09% by weight of vinyl functional groups.
[0074] In a fifth embodiment, the method of the first or second embodiment further comprises the step of: (B) providing a second alkenyl-containing polydialkylsiloxane gum having a unit formula (II): (R 1 2R 2 SiO 1 / 2 ) h (R 1 3SiO 1 / 2 ) i (R 1 R 2 SiO 2 / 2 ) j (R 1 2SiO 2 / 2 ) k wherein each R 1 are independently an alkyl group of 1 to 10 carbon atoms, and each R 2 are independently alkenyl groups of 2 to 6 carbon atoms, and the subscripts h, i, j, and k represent the average number of each unit in the unit formula and have values such that 2≧h≧0, 2≧i≧0, 100≧j≧21, 10,000≧k≧2,000, and the amount (h+i)=2.
[0075] In a sixth embodiment, the method of the first or second embodiment further comprises the step of: (B) a second alkenyl-containing polydialkylsiloxane gum is present and has 0.5% to 0.9% by weight vinyl functionality.
[0076] In the seventh embodiment, in the method of the first or second embodiment, the weight ratio calculated by (B) / [(A)+(B)] is 0 to 0.43.
[0077] In an eighth embodiment, in the method of the first or second embodiment, the weight ratio calculated by [(A)+(B)] / (C) is >0 to 0.43.
[0078] In a ninth embodiment, in the method of the first or second embodiment, the (C) alkenyl-containing polydialkylsiloxane polymer is represented by the unit formula (III): (R 1 2R 2 SiO 1 / 2 ) l (R 1 3SiO 1 / 2 ) m (R 1 R 2 SiO 2 / 2 ) n (R 1 2SiO 2 / 2 ) o wherein each R 1 are independently an alkyl group of 1 to 10 carbon atoms, and each R 2 are independently alkenyl groups of 2 to 6 carbon atoms, and the subscripts l, m, n, and o represent the average number of each unit in the unit formula and have values such that 2≧l≧0, 2≧m≧0, 100≧n≧0, 1,000≧o≧10, and the amount (l+m)=2.
[0079] In a tenth embodiment, in the method of the first or second embodiment, the weight ratio calculated by [(A)+(B)] / (C) is 0.6 to 1.5.
[0080] In an eleventh embodiment, in the method of the first or second embodiment, the weight ratio calculated by [(A)+(B)] / (C) is 0.6 to 1.3.
[0081] In a twelfth embodiment, in the method of the first or second embodiment, the weight ratio calculated by [(A)+(B)] / (C) is 0.7 to 1.2.
[0082] In a thirteenth embodiment, the method of the first or second embodiment, wherein the vulnerable layer is a passivation layer.
[0083] In a fourteenth embodiment, the method of the first or second embodiment, wherein the frangible layer is a thin film encapsulation layer.
Claims
1. 1. A pressure sensitive adhesive composition comprising: (A) a first alkenyl-containing polydialkylsiloxane gum having silicon-bonded alkyl groups having 1 to 10 carbon atoms and silicon-bonded alkenyl groups having 2 to 6 carbon atoms, the vinyl functionality being present in an amount of 0.03% to 0.11% by weight based on the weight of the first alkenyl-containing polydialkylsiloxane gum; optionally, (B) a second alkenyl-containing polydialkylsiloxane gum having silicon-bonded alkyl groups having 1 to 10 carbon atoms and silicon-bonded alkenyl groups having 2 to 6 carbon atoms, the vinyl functionality being present in an amount of 0.3% to 1.1% by weight based on the weight of the second alkenyl-containing polydialkylsiloxane gum; wherein starting materials (A) and (B) are present in amounts sufficient to provide a weight ratio, calculated by (B) / [(A)+(B)], of from 0 to 0.5; (C) an alkenyl-containing polydialkylsiloxane polymer having silicon-bonded alkyl groups having 1 to 10 carbon atoms and silicon-bonded alkenyl groups having 2 to 6 carbon atoms, the vinyl functionality being present in an amount of 0.01% to 2% by weight based on the weight of the alkenyl-containing polydialkylsiloxane polymer; wherein the starting materials (A), (B), and (C) are present in amounts to provide a weight ratio calculated by [(A)+(B)] / (C)] of from 0.5 to 2.5; (D) a polyalkylhydrogensiloxane having silicon-bonded alkyl groups having from 1 to 10 carbon atoms, at least 3 silicon-bonded hydrogen atoms per molecule, and an average of at least 1 weight percent silicon-bonded hydrogen atoms; (E) a platinum group metal catalyst in an amount sufficient to provide a concentration of 10 to 5000 ppm by weight of Pt group metal in said composition; (F) an acetylenic alcohol; optionally, (G) an adhesion promoter; and (H) 10% to 90% by weight of an organic solvent, based on the total weight of all starting materials in the composition; A pressure sensitive adhesive composition provided that all of the starting materials in said composition combined have a molar ratio of silicon-bonded hydrogen atoms to silicon-bonded alkenyl groups (SiH / Vi ratio) of from 3.33 to 5.
21.
2. (A) the first alkenyl-containing polydialkylsiloxane gum has a unit formula (I): 1 2 R 2 SiO 1/2 ) d (R 1 3 SiO 1/2 ) e (R 1 R 2 SiO 2/2 ) f (R 1 2 SiO 2/2 ) g wherein each R 1 is independently an alkyl group of 1 to 10 carbon atoms; 2 is independently an alkenyl group of 2 to 6 carbon atoms, and the subscripts d, e, f, and g represent the average number of each unit in the unit formula and have values such that 2≧d≧0, 2≧e≧0, 20≧f≧5, 10,000≧g≧2,000, and the amount (d+e)=2.
3. (B) the second alkenyl-containing polydialkylsiloxane gum is present, the second alkenyl-containing polydialkylsiloxane gum having a unit formula (II): 1 2 R 2 SiO 1/2 ) h (R 1 3 SiO 1/2 ) i (R 1 R 2 SiO 2/2 ) j (R 1 2 SiO 2/2 ) k wherein each R 1 is independently an alkyl group of 1 to 10 carbon atoms; 2 is independently an alkenyl group of 2 to 6 carbon atoms, and the subscripts h, i, j, and k represent the average number of each unit in the unit formula and have values such that 2≧h≧0, 2≧i≧0, 100≧j≧21, 10,000≧k≧2,000, and the amount (h+i)=2.
4. The composition of any one of claims 1 to 3, wherein (A) the first alkenyl-containing polydialkylsiloxane gum has from 0.05% to 0.09% by weight vinyl functionality.
5. 5. The composition of claim 1, wherein (B) the second alkenyl-containing polydialkylsiloxane gum is present and has from 0.5% to 0.9% by weight vinyl functionality.
6. (C) the alkenyl-containing polydialkylsiloxane polymer has the unit formula (III): (R 1 2 R 2 SiO 1/2 ) l (R 1 3 SiO 1/2 ) m (R 1 R 2 SiO 2/2 ) n (R 1 2 SiO 2/2 ) o wherein each R 1 is independently an alkyl group of 1 to 10 carbon atoms; 2 is independently an alkenyl group of 2 to 6 carbon atoms, and the subscripts l, m, n, and o represent the average number of each unit in the unit formula and have values such that 2≧l≧0, 2≧m≧0, 100≧n≧0, 1,000≧o≧10, and the amount (l+m)=2.
7. 7. The composition according to claim 1, wherein the weight ratio calculated by [(A)+(B)] / (C) is between 0.6 and 1.
3.
8. (D) the polyalkylhydrogensiloxane has the unit formula (IV): (R 1 3 SiO 1/2 ) 3 (R 1 2 SiO 2/2 ) p (R 1 HSiO 2/2 ) q wherein each R 1 is independently an alkyl group of 1 to 10 carbon atoms, and the subscripts p and q represent the average number of each difunctional unit in the unit formula and have values such that 0≦p≦2,000 and 2≦q≦2000.
9. (E) The composition of any one of claims 1 to 8, wherein the catalyst comprises a complex of chloroplatinic acid and divinylsiloxane.
10. The composition of any one of claims 1 to 9, wherein the acetylenic alcohol comprises ethynylcyclohexanol.
11. 11. The composition of any one of claims 1 to 10, wherein the composition is a multi-part composition comprising a base and a hardener part, the base comprising starting materials (A) and (D), the hardener part comprising starting materials (A) and (E), and the composition further comprising starting material (F) in one or more of the base or a separate third part.
12. 1. A method comprising: Optionally, 1) treating a surface of a substrate; 2) applying a pressure sensitive adhesive composition according to any one of claims 1 to 10 to the substrate; and 3) drying the pressure-sensitive adhesive composition to remove all or a portion of the solvent; and 4) curing the pressure sensitive adhesive composition to form a pressure sensitive adhesive film.
13. 13. A method of fabricating a flexible organic light emitting diode device, the method comprising applying the pressure sensitive adhesive prepared in the method of claim 12 to a passivation layer in the device.
14. 14. A pressure sensitive adhesive film prepared by the method of claim 13.
15. 15. Use of the pressure-sensitive adhesive film according to claim 14 for protecting a passivation layer in a flexible organic light-emitting diode device.
Citation Information
Patent Citations
Pressure-sensitive adhesives and their preparation and use
JP2021535936A
Silicone pressure-sensitive adhesive and laminate having silicone pressure-sensitive adhesive layer
WO2016139956A1
Silicone adhesive agent composition, and adhesive tape or adhesive film using same
WO2020026844A1
Silicone pressure sensitive adhesive composition and preparation and use thereof in protective films for ultrasonic fingerprint sensors
WO2020248181A1